Student Difficulties in Learning Islamic Religious Education - Uswatun Hasanah; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Not a few students experience obstacles or difficulties in their learning process. These difficulties are unnatural conditions in the form of threats, obstacles or disturbances that result in a psychological syndrome that causes a person to experience learning difficulties. Unnatural conditions can come from internal factors in the form of health or physical disorders as well as psychological or mental disorders, or external factors originating from the environment, whether in the family, school or social environment. The results of this research were obtained using a library approach which focuses on data obtained through a collection of articles and those related to them. The types of student learning difficulties that are often encountered are a) learning disorder, b) learning dysfunction, c) under achiever, d) slow learner, and e) learning disabilities, accompanied by varying symptoms.